THE RELATIONSHIP BETWEEN LEARNING INDEPENDENCE AND LEARNING FACILITIES WITH STUDENT LEARNING OUTCOMES - Siti Nursolekah; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2018)
The results of the student's mathematics learning associated with many factors. Learning independent and learning facilities factors that may be associated with mathematics learning outcomes of students. This study aims to determine whether or not a positive and significant relationship between learning independent and learning facilities with mathematics learning outcomes in students class VIII at State Senior High School (SMA Negeri) 3 Pandak Bantul in the odd semester of the academic year 2017/2018. The population in this study was all eighth-grade students at SMP Negeri 3 Pandak Bantul in the odd semester of the academic year 2017/2018, which consists of 4 classes with 118 students as a sample class was class VIII A, which consists of 30 students using a random sampling technique to the class. Data collection techniques used questionnaires and tests—the instruments using validity, reliability testing, and test different power. Test requirements analysis was used the normality test, the independent test, and the linearity test. Data analysis for hypothesis testing used correlation analysis and linear regression analysis. The results showed that there is a positive and significant relationship between learning independent (X1) and learning facilities (X2) with mathematics learning outcomes with means with R = 0,7735 and R2 = 0,5984 with . and RC (X1) = 24,6517 %, RC (X2)= 75,3483 %, EC (X1) = 14,7520 %, EC (X2)=45,0896%.